Proposição de conjunto de diretrizes para mitigar barreiras e dificuldades na implantação do e-commerce no pequeno e médio varejista - Nogueira, Edithe Oliveira (Universidade do Vale do Rio dos Sinos, 2023)
This research has the general objective proposing a set of guidelines to mitigate the barriers and difficulties in the implementation and operations of e-commerce in small and medium retailers. The accelerated growth of electronic commerce, also known as e-commerce, has become an important competitive advantage for companies, translating into a new alternative for people to make their purchases on websites quickly and easily. With the growth of the use of electronic commerce in the world, the problems faced with this new commercial modality also grow. This research exposes the challenges regarding e-commerce, and the main difficulties and internal and external barriers encountered by customers using this tool in the e-commerce network. This research is exploratory and qualitatively described, with field research interpreted by content analysis, using interviews with managers and companies that operate with a technological platform in the e-commerce modality. It is considered that, with the high growth of this type of commerce on the internet, the need for organizations to plan an adequate model that supports the entire system also grows, since there is a large number of companies that adhere to the e-commerce system.
Keywords: E-commerce; Bussines-to-consumer; B2C; PMEs varejistas; Tecnologias; Dificuldades e barreiras; Retail SMEs; Technologies; Difficulties and barriers; ACCNPQ::Engenharias::Engenharia de Produção